High-Linearity Dual-Parallel Mach–Zehnder Modulators in Thin-Film Lithium Niobate - Tao Yang; Lutong Cai; Zhanhua Huang; Lin Zhang (Photonics, 2024)
Microwave photonic (MWP) systems are inseparable from conversions of microwave electrical signals into optical signals, and their performances highly depend on the linearity of electro-optic modulators. Thin-film lithium niobate (TFLN) is expected to be an ideal platform for future microwave photonic systems due to its compact size, low optical loss, linear electro-optic effect, and high bandwidth. In this paper, we propose a TFLN modulator with a low voltage–length product (VπL) of 1.97 V·cm and an ultra-high-linearity carrier-to-distortion ratio (CDR) of 112.33 dB, using a dual-parallel Mach–Zehnder interferometer configuration. It provides an effective approach to fully suppress the third-order intermodulation distortions (IMD3), leading to 76 dB improvement over a single Mach–Zehnder modulator (MZM) in TFLN. The proposed TFLN modulator would enable a wide variety of applications in integrated MWP systems with large-scale integration, low power consumption, low optical loss, and high bandwidth.